Standar Akuntansi Keuangan (PSAK) 102 Tentang Pembiayaan Murabahah Dalam Penerapan Akuntansi Syariah Pada PT. Bank Pembiayaan Rakyat Syariah Metro Madani - Anwar L Nata, Andrian (Sekolah Tinggi Agama Islam Ma`arif Kalirejo Lampung Tengah, 2023)
The purpose of this study is to determine the recognition and measurement of murabahah transactions based on PSAK 102 at PT. Metro Madani Sharia People's Financing Bank, presentation of murabahah transactions based on PSAK 102 at PT. Metro Madani Sharia People's Financing Bank, disclosure of murabahah transactions based on PSAK 102 at PT. Metro Madani Sharia People's Financing Bank. Related to the research title, this research was conducted using field research methods with a qualitative approach. Based on the results of the research and discussion, it is known that murabaha transactions can be made through orders or without orders. However, this found that the. condition in the bank only entered into a murabaha contract after receiving an order from a customer. The item is recognized as a murabaha asset inventory. At the time of acquisition, murabahah assets are recognized as inventories at cost. At the time of the murabahah contract, murabahah receivables are recognized at the acquisition cost of murabahah assets plus the agreed profit. At the end of the financial reporting period, murabahah receivables are valued at net realizable value, namely the balance of receivables less allowance for possible losses on receivables. The murabahah assets are measured at cost. Murabaha assets will not experience an impairment due to wear and tear before being given to the customer. This research is because the goods are not held first by the bank but are held directly by the customer. Presentation of murabahah receivables in the balance sheet is the amount of net realizable value, namely the balance of murabahah receivables minus allowance for possible losses on receivables. Deferred murabahah margin is presented as a deduction for murabahah receivables. Deferred murabahah expenses are presented as a deduction from murabahah payables. Murabahah receivables have been disclosed in the balance sheet at net realizable value. Murabahah receivables are disclosed at net realizable value. The deferred murabaha margin has been presented in the profit or loss report, so that it is in accordance with the Statement of Financial Accounting Standards. Suggestions in this study are for PT. Metro Madani Syariah People's Financing Bank to be able to present financial reports that are not based on OJK or make two complete financial reports, namely financial reports according to OJK and financial reports according to PSAK 102. For further research so that the data obtained is more valid, it is necessary to pay attention to the recording of related journals with murabaha.